Incarceration of the Gravid Uterus in Women with Previous Cesarean Section: Case Series and Literature Review - Yun F; Fu L; Wen J; Chen D; Wang F (International Journal of Women's Health, 2025)
Feng Yun,1 Leyi Fu,1 Jie Wen,1 Danqing Chen,1,3 Fangfang Wang1– 4 1Women’s Hospital, School of Medicine, Zhejiang University, Hangzhou, 310006, People’s Republic of China; 2Key Laboratory of Reproductive Genetics (Zhejiang University), Ministry of Education, Hangzhou, 310058, People’s Republic of China; 3Zhejiang Key Laboratory of Maternal and Infant Health, Hangzhou, 310006, People’s Republic of China; 4Linhai Branch, Women’s Hospital, School of Medicine, Zhejiang University, Linhai, 317099, People’s Republic of ChinaCorrespondence: Fangfang Wang, Department of Obstetrics, Women’s Hospital, School of Medicine, Zhejiang University, 1 Xueshi Road, Hangzhou, Zhejiang, 310006, People’s Republic of China, Email drwangfangfang@zju.edu.cnAbstract: Incarceration of the gravid uterus (IGU) is a rare and serious condition associated with significant maternal and fetal morbidities. Its occurrence in women with a history of cesarean section (CS) poses a great challenge to obstetricians. We report two cases: Case 1 presented with acute urinary retention at 11 weeks of gestation, with IGU diagnosis ultimately established at 15 weeks following persistent symptoms. Initial manual reduction attempts failed, but resolution occurred later. Case 2 developed severe urinary retention at 16 weeks, and the uterus was repositioned after Foley catheter placement. Both patients underwent uncomplicated cesarean deliveries at term. To delineate the clinical characteristics and optimal management of this condition, we conducted a comprehensive literature review and identified 29 additional cases reported over the past 40 years. Analysis revealed a median gestational age of 17 weeks at presentation and 37 weeks at delivery or pregnancy termination. Among them, 16 had one or more risk factors in addition to previous CS. Clinical presentation and treatment methods paralleled those described in non-CS patients. Successful resolution with favorable outcomes was achieved in 19 cases, with interventions initiated before 20 weeks demonstrating a higher resolution rate. Severe maternal complications occurred in 30% of cases, predominantly in unresolved ones, including two uterine ruptures. Early diagnosis and active management are crucial for optimizing obstetric outcomes and reducing maternal complications in these patients.Keywords: incarcerated retroverted uterus, cesarean section, pregnancy outcomes, uterine rupture